PTU-101 First demonstration of trainee-led networks delivering quality improvements in gastroenterology services: a call to action. (8th June 2018) - ; Ingram, Richard
Abstract : Introduction: The GARNet was the first trainee-led gastroenterology network to complete a multi-site audit. We focussed on standards of care and outcomes in acute upper GI bleeding (AUGIB). Here, we present our regional experience with quality improvement (QI) and our subsequent re-audit. Methods: We audited patient care against national standards (NICE CG141 and QS38). Patients aged ≥16 years admitted with suspected AUGIB who underwent an inpatient OGD were prospectively identified between 01–30/11/16 and 01–30/11/17. QI focused on reducing time from presentation to endoscopy, using process mapping and staff questionnaires, to develop local action plans at each site. Fishers, Mann-Whitney and Wilcoxon tests were used for categorical, unpaired and paired continuous variables respectively. Results: See Table 1. 7 sites were able to participate in both rounds. There was a significant increase in the documentation of GBS and rebleed plans (vs. audit standard of 100%). There were non-significant reductions in the median time to OGD and the proportion within 24 hour. This improved at 5 sites (p>0.05 in paired analysis), and 5 vs. 6 sites achieved JAG 50% standard (no sites achieved 75% standard). In the 2017 cohort, 42% of patients had OGD delayed >24 hour. They had significantly lower GBS and longer length of stay (see Table 2). In patients receiving endotherapy, OGDs were more timely (18.4 hour [11.3–25.9] vs. 22.8 hour [16.9–43.5], p=0.005) but 31% were still treated after 24 hour. Conclusions: Locally-tailored QI driven through regional trainee-led audit can deliver modest improvements in patient care. This audit shows that further action is needed to meet standards. Time to OGD is a pragmatic measure of quality of care and not a clinical outcome. Service development would benefit greatly from a tool to identify patients most likely to benefit from timely endoscopic diagnosis and endotherapy. We propose that QI is co-ordinated at national level. We are collaborating with our fellow trainee networks to support such initiatives.